2017
DOI: 10.1021/acs.inorgchem.6b02819
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Lanthanide(III) Complexes Constructed from Azobenzene Derivative and β-Diketone Ligands: Luminescent, Magnetic, and Reversible Trans-to-Cis Photoisomerization Properties

Abstract: The coordination ability of ligands functionalized by azobenzene was manipulated, and two novel chelating ligands, (E)-4-(phenyldiazenyl)-N,N-bis(pyridin-2-ylmethyl) benzohydrazide (CHNO, PBPM) and (E)-4-((4-(dimethylamino)phenyl)diazenyl)-N,N-bis(pyridin-2-ylmethyl) benzohydrazide (CHNO, dmPBPM), were synthesized. The ligands can offer four coordinating atoms (one oxygen and three nitrogens) to act as tetradendate ligands, together with the two β-diketonates (4,4,4-trifluoro-1-phenylbutane-1,3-dionate, tfd), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 62 publications
4
43
0
Order By: Relevance
“…We subsequently manipulated the ligands and designed ( E )-4-(phenyldiazenyl)- N , N -bis(pyridin-2-ylmethyl) benzohydrazide lanthanide complexes. 20 We detected trans-to-cis photoisomerization and visible emission of 614 nm from Eu 3+ in the complexes in solution. This is remarkable, although it is not very useful from a practical biological viewpoint, owing to the strong optical interference generated by the biological samples.…”
Section: Introductionmentioning
confidence: 88%
“…We subsequently manipulated the ligands and designed ( E )-4-(phenyldiazenyl)- N , N -bis(pyridin-2-ylmethyl) benzohydrazide lanthanide complexes. 20 We detected trans-to-cis photoisomerization and visible emission of 614 nm from Eu 3+ in the complexes in solution. This is remarkable, although it is not very useful from a practical biological viewpoint, owing to the strong optical interference generated by the biological samples.…”
Section: Introductionmentioning
confidence: 88%
“…On/off fluorescent switching [15] and photostabilization [16] via reversible cis-trans isomerization have been also reported. [17] Photo-induced polymerization [18] as well as cis-trans photoisomerization studies [19] in the presence of silsesquioxane nano-cages have been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, configurational changes can be associated with different fluorescence emissions regulated by the photoisomerization process. On/off fluorescent switching and photostabilization via reversible cis‐trans isomerization have been also reported . Photo‐induced polymerization as well as cis‐trans photoisomerization studies in the presence of silsesquioxane nano‐cages have been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cis-form is unstable and liable to reversely isomerize to trans-form under the action of visible light or slight heat (Henzl et al, 2006 ; Kumar and Suresh, 2009 ; Schmidt et al, 2010 ). Given the fact that cis- and trans-isomers of azobenzenes have a different spatial arrangement of the aromatic moieties, physical and chemical properties of azobenzenes varied a lot, some examples being π-π stack interaction among molecules, dipole moments, and surface wettability (Li et al, 2014 ; Yuan et al, 2014 ; Lin et al, 2016 , 2017 ). Consequently, azobenzenes became particularly popular as photoresponsive chromophores in a number of research fields including biomedical fields (Deka et al, 2015 ; Liu et al, 2015 ; Bian et al, 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%